Association of decreased myonectin levels with metabolic and hormonal disturbance in polycystic ovary syndrome. (1st November 2020) - Demir, İsmail and Guler, Aslı
Abstract: Myonectin is a myokine involving in glucose and lipid metabolisms. Polycystic ovary syndrome (PCOS) is a metabolic and reproductive disorder associated with insulin resistance. Our aims were to discover whether myonectin levels were altered in PCOS women comparing to controls and to determine the link of myonectin with hormonal-metabolic parameters in PCOS women. The current research was designed as a case-control study. Seventy-two subjects with PCOS and 72 age- and body mass index (BMI)-matched subjects as controls were enrolled into the study. Circulating myonectin levels were measured by ELISA. Myonectin levels were significantly lower in PCOS subjects compared to controls (6.77 ± 1.96 vs. 9.14 ± 2.87 ng/ml, p < .001). Myonectin exhibited an inverse association with BMI, insulin resistance, free androgen index (FAI) and triglycerides whereas it showed a positive association with high-density lipoprotein cholesterol (HDL-C) in women with PCOS. Logistic regression analysis revealed that decreased myonectin levels were parallel with increased probability of having PCOS risk. Decreased myonectin levels were associated with metabolic and hormonal disturbances in PCOS women, suggesting that myonectin may play a role in pathophysiology of PCOS.